Interpreting Students' Reading Comprehension Strategies in Higher Education - Eripuddin; Rahayu, Pipit; Azi Nurazima Juhastri; Evi Peranian; Evi Kasyulita (English Lecturers and Teachers Association (ELTA), 2025)
Reading comprehension is a fundamental skill that enables students to extract meaning from Reading comprehension is a crucial skill that enables students to extract meaning from texts, supporting their academic success, professional growth, and cognitive development. This qualitative study explores the reading comprehension strategies of eighth-grade students at Al-Khoir Islamic Boarding School in Padang Lawas, with data collected from 22 students through questionnaires and structured interviews. The results reveal that skimming and scanning are the dominant techniques, with skimming being the most frequently used method. About 50% of participants expressed that these strategies were effective due to their simplicity and speed in aiding text comprehension, with skimming receiving the highest score among the four strategies assessed. While these strategies allow for efficient reading, the study suggests that students engage less with more comprehensive techniques like intensive and extensive reading, which are essential for fostering deeper comprehension and critical thinking skills. This preference for skimming and scanning may be influenced by the boarding school’s structured environment, which creates time pressures, as well as the students' language proficiency, which may limit their ability to engage with more complex texts. The findings emphasize the need for instructional strategies that promote a balanced approach, integrating both surface-level and in-depth reading techniques to enhance overall language proficiency. Keywords : Reading Strategies; Reading Comprehension; Al-Khoir Boarding School